Morphine decreases social interaction of adult male rats, while THC does not affect it - Šlamberová, Romana; Mikulecká, Anna; Macúchová, Eva; Hrebíčková, I; Ševčíková, Mária; Nohejlová, Kateryna; Pometlová, Marie (Physiological research, 2016)
The aim of the present study was to compare effect of three low doses of morphine (MOR) and delta9-tetrahydrocannabinol (THC) on social behavior tested in Social interaction test (SIT). 45 min prior to testing adult male rats received one of the drugs or solvents: MOR (1; 2.5; 5 mg/kg); saline as a solvent for MOR; THC (0.5; 1; 2 mg/kg); ethanol as a solvent for THC. Occurrence and time spent in specific patterns of social interactions (SI) and non-social activities (locomotion and rearing) was video-recorded for 5 min and then analyzed. MOR in doses of 1 and 2.5 mg/kg displayed decreased SI in total. Detailed analysis of specific patterns of SI revealed decrease in mutual sniffing and allo-grooming after all doses of MOR. The highest dose (5 mg/kg) of MOR decreased following and increased genital investigation. Rearing activity was increased by lower doses of MOR (1 and 2.5 mg/kg). THC, in each of the tested doses, did not induce any specific changes when compared to matching control group (ethanol). However, an additional statistical analysis showed differences between all THC groups and their ethanol control group when compared to saline controls. There was lower SI in total, lower mutual sniffing and allo-grooming, but higher rearing in THC and ethanol groups than in saline control group. Thus, changes seen in THC and ethanol groups are seemed to be attributed mainly to the effect of the ethanol. Based on the present results we can assume that opioids affect SI more than cannabinoid.
Keywords: krysa rodu Rattus; Animals; interpersonální vztahy; Dronabinol; morfin; lokomoce; Interpersonal Relations; mužské pohlaví; zvířata; Morphine; tetrahydrokanabinol; Male; Rats, Wistar; Locomotion; Rats; potkani Wistar